THE EFFECT OF HARDINESS ON STRESS IN MOTHERS IN HELPING ELEMENTARY SCHOOL CHILDREN IN TAMAN SARI DISTRICT - Suhana Suhana; Ria Dewi Eryani; Agus Budiman (Pusat Penerbitan Universitas (P2U) Unisba, 2021)
During the Covid 19 pandemic, distance learning (PJJ) was applied, this made parents face different situations than usual, mothers felt difficult, annoyed, dizzy, quick to anger, signs of stress symptoms. However, there are also mothers who live it with enthusiasm to overcome it, because they feel that their children's achievements are their responsibility, and are challenged to improve their ability to accompany children. This shows the characteristics of the hardiness personality. Hardiness is the individual's personality to turn stressful conditions into opportunities for growth and development. The purpose of the study was to determine how much influence hardiness has on stress in mothers. The research method uses a quantitative approach, with simple linear regression analysis. The research subjects were 240 people using a hardiness measuring instrument based on the theory of Kobasa and Maddi and a Perceived Stress Scale-10 (PSS-10) stress measuring instrument. The results showed that there was an effect of hardiness on stress in mothers who helped their children in distance learning activities.